Review on Dynamic Behaviour of Moored Twin Hulls FPSO - Nik Ismail, Nik Mohd Khairuddin B.; Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
The development of floating offshore structures have been successfully and rapidly in many years. Many researchers has studied the dynamic behavior of of moored floating production storage and offloading structure. This paper investigated the dynamic behavior of catenary anchor leg moored twin hulls floating production storage and offloading which subjected to sea waves, in order to get insight knowledge on its dynamic behaviours due to various turret locations with different loading conditions. The comparison of the dynamics behaviour to the FPSO and it mooring lines are important when choosing potential development and optimal options. The research founded that it currently no information is available for the comparison of the dynamic behaviour of the internal turret moored of twin hulls FPSO at different loading conditions with various turret locations under the action of wave.